TELAAH SOAL UJIAN AKHIR BERSTANDAR NASIONAL MATA PELAJARAN BAHASA ARAB MADRASAH ALIYAH (MA) TAHUN PELAJARAN 2012/2013 - Sutarjo, J. (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STAIN Jurai Siwo Metro, 2014)
The evaluation was conducted in an integrated manner with the learning activities. evaluation can be done both in formal and informal atmosphere, in the classroom, outside the classroom, integrated in the teaching and learning activities or done at that particular time. The evaluation was conducted through a variety of means, such as written tests, assessment of studentsâ work through a collection of work (work) students (work-sheet), and evaluation work present (performance)of students. In this study using the technique of documentation in the form of draft national final exam Madrasah Aliyah (MA) inÂ 2012/2013. This study used a qualitative method, which seeks to describe about the quality of the test items the national final exam Madrasah Aliyah (MA) in 2012/2013 in termsÂ of validity andthe reliability, the degree of difficulty of items, distinguishing items, andÂ functionof troublemaker, and compliance problems with standards of competence andÂ competence base. From the analysis conducted, it appears that in terms of materialsÂ and construction aspects of the study exam final exam national standard Arabic subjectsÂ Madrasah Aliyah (MA) in 2012/2013 in general is still not good. While looking at theÂ aspects of language study exam nationally standardized final exam subjects ArabicMadrasah Aliyah (MA) in 2012/2013 in general is good.Keywords: The evaluation, national final exam, Madrasah Aliyah